Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Pelanggan Terhadap PT Continental Industry Supply - Wijaya, Fredric; Purba, Tiurniari (MOTIVASI, 2020)
ABSTRACT Purpose - Regarding marketing, brand image is a meaningful part so that it has a lot of impact on customers so they can buy because customer direction takes precedence on branded and achieved goods. But the brand image, product quality also gives a part thatinfluences the desire of the customer to buy when running a product, not  just looking  at  value  in the aspect of quality, or  the brand and quality still influences with the brand image that is closely related to a particular product. This study uses the influence of brand image and product quality on customer purchasing decisions on PT Continental Industry Supply.Design/methodology - Descriptive research design and quantitative approach along with data dissemination is data used by researchers to carry out a way of distributing questionnaires to respondents. Non-probability sampling and saturated sampling techniques are tools used by researchers to examine a sample of 130 respondents on a questionnaire to spread to respondents, To find out the results analyzed and linear regression analysis using research has used SPSS version 25 as a number calculation equipment program.Findings - Regarding the calculation results, it is known that brand image (X1) is partially similar and has a positive and significant influence on purchasing decisions (Y) with a significant value of 0,000<? 0.05. Product quality (X2) is similar to partial and positive and significant influence on purchasing decisions (Y) with a significant value of 0,000 <? 0.05. Brand Image (X1) and Product Quality (X2) simultaneously have positive and significant influence on purchasing decisions (Y) with a significant value of 0,000 <? 0.05.